(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The Zamin State Reserve, located on the western spurs of the Turkestan Range in the upper reaches of the Sangzar River,is the richest region of Uzbekistan in floristic and phytocenotic terms. This reserve, established in 1926, is unique in the number of rareendangered plant species growing in this small area. Juniper forests, in their completeness and richness of tree and shrub species, haveno analogues in our republic. At least 20 plant species have been described from this territory, which is comparable to the most famousflora of Chimgan. List of vascular plants compiled and published by M.G. Popov, N.V. Androsov in 1937, for a long time was almostthe only floristic information throughout the Western Pamirs. In the second half of the 20th century, large-scale floristic studies werecarried out not only in this region, but also throughout the territory of Uzbekistan. In particular, lists of floras of the Chatkal, Nurataand Surkhan reserves were published. Thus, the dendroflora studied by us, richer in the number of plant species, will be a good help forcreating an electronic database of the modern flora of Uzbekistan.